Psychoanalysis in the Novel Garis Luka by Khairani Hasan - Suryani, Ifa; Rahayu, Sri (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: A character's personality shapes a compelling and high-quality novel. It not only drives the storyline and deep insights into human nature, emotions, and experiences, allowing readers to connect with the narrative on a profound level. Aims: This research examines the significance of the characters' personality traits in Khairani Hasan's novel